Academic Advisors as Valuable Partners for Supporting Academic Integrity - Javeed, Shehna (Canadian Perspectives on Academic Integrity, 2018)
Academic Integrity is a fundamental value in higher education. Due to the increased ease of access to all types of information through social media and the internet, the lines have become blurred on what is can be “borrowed” and used. Recent proliferation of contract cheating has only reinforced that integrity cannot be just the responsibility of the Dean’s Office or the Academic Integrity offices. Advisors and learning strategists who see students regularly, can ubiquitously play a valuable role in integrating academic honesty into their conversations and workshops. This can be achieved in collaborations with campus partners on campus wide programming, starting early with integrating the conversation about honesty in academic orientations for new students and parents, and when having difficult conversations about study success and academic decision-making.